Trauma team activation and triage of severely injured patients at one non-trauma-center hospital in Stockholm - Oscar Lapidus; Denise Bäckström; Folke Hammarqvist; Andreas Wladis; Rebecka Rubenson Wahlin (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background In 2017 the Swedish public insurance company Löf published national guidelines for in-hospital trauma team activation (TTA), which are now widely adopted in Sweden. No studies have examined triage accuracy at non-trauma-center hospitals in the Stockholm trauma system since the implementation of the new TTA criteria. Aim To assess trauma triage accuracy at one non-trauma-center hospital in Stockholm. Methods 3528 trauma patients treated at Södersjukhuset during 2019–2022 were acquired from the Swedish Trauma Registry (SweTrau) to calculate TTA triage accuracy. Undertriage was defined in accordance with national guidelines as patients with a New Injury Severity Score > 15 who did not prompt level 1 TTA on arrival to hospital. Results In total there were 849 severely injured patients during the study period, of which 2.2% (n = 19) prompted TTA level 1, corresponding to an undertriage of 98% (n = 830). Of the 849 severely injured patients, 41% (n = 348) prompted TTA level 2 whereas the remaining 57% (n = 482) prompted no TTA on arrival to hospital. There were a total of 3046 patients prompting TTA during the study period, but only 19% (n = 19) of level 1 and 12% (n = 348) of level 2 patients were severely injured, and 45% had a NISS ≤ 3. Conclusion Undertriage of severely injured trauma patients was 98% according to the definition specified by Swedish trauma triage guidelines, higher than reasonably acceptable. There is considerable overtriage with non-severely injured patients prompting TTA. However, the suitability of using NISS > 15 to retrospectively define the need for TTA is debatable as this does not always correlate with the fulfillment of the TTA criteria. Further investigation of adherence to trauma triage guidelines in clinical practice may be of value to improve triage accuracy in organized regional trauma systems.